Effects of maternal aspirin treatment on hemodynamically significant patent ductus arteriosus in preterm infants – pilot study. (4th March 2022) - Fridman, Elena; Mangel, Laurence; Mandel, Dror; Beer, Gil; Kapusta, Livia; Marom, Ronella
Abstract: Aim: To assess the burden of hemodynamically significant patent ductus arteriosus (hs-PDA) in preterm infants exposed to aspirin in utero . Methods: We retrospectively reviewed the medical records of 21 preterm infants <34 weeks whose mothers were treated with aspirin during gestation, and were screened for patent ductus arteriosus due to severe respiratory distress syndrome and the need for positive pressure ventilation. These infants were compared to 42 preterm infants born without exposure to aspirin in utero . Results: We found significantly lower frequency of hs-PDA and higher rate of successful pharmacological PDA closure after single course of ibuprofen treatment along with significantly lower cumulative doses of ibuprofen in the study group. Furthermore, PDA closure was achieved significantly earlier in the study group (day 4 versus 11, p = .02). Conclusion: Aspirin treatment during pregnancy seemed to reduce the incidence of hs-PDA in preterm infant and to increase infant responsiveness to postnatal medical treatment of PDA.